PENUNDAAN PELAKSANAAN PEMILIHAN UMUM PRESIDEN/WAKIL PRESIDEN DAN PERPANJANGAN MASA JABATAN PRESIDEN/WAKIL PRESIDEN MENJADI 3 (TIGA) PERIODE DALAM PERSPEKTIF TEORI KONSTITUSI DAN UUD 1945 AMANDEMEN - Elwidarifa Marwenny; Roby Syafwar; Desi Sommaliagustina (Ensiklopedia of Journal, 2023)
Two years from now, Indonesia will hold a democratic party for the Presidential Election in 2024, which is the 2024-2028 leadership period, on February 14, 2024. In relation to this election, the political elites and political parties have begun to propose a postponement of the holding of the Presidential and Vice Presidential Election and the issues of the position of President and Vice President will be extended to three periods. The history of postponing election has happened in Indonesia, however, it was based on the reasons for postponing which have a clear constitutional basis. In the Amendment of the 1945 Fundamental Constitution, there is no regulation regarding the postponement of the implementation of the Presidential Election or the President who held the government for approximately three periods. Nevertheless, what if the political elite’s decision is motivated by the economic situation, which is still recovering from COVID-19. Therefore, the writers are interested in discussing: (1) The postponement of the implementation of the Presidential Election in Indonesia and the extension of the President’s term of office to three periods is related to the Constitution theory; (2) The legal implications of postponing the implementation of the Presidential and Vice Presidential Election and the extension of the term of office of the President and Vice President Election to three periods in the perspective of the Amendment of the 1945 Fundamental Constitution. The writers conduct a survey of the relevant literature using a normative juridical approach to resolve this research. So as to obtain the conclusion: (1) The Amendments to the constitution can be made as long as they meet the indicators for amending the constitution, which include the existence of urgent reasons for amendments, obtaining support from the people for amendments, and the existence of social, political, and economic conditions which cause changes to occurs; (2) If wish to postpone further elections or extend the Presidential term to three periods, it must be constutional, so if the constitution must change its function, it is not to maintain power but to overcome the existing problems.Keywords: The Presidential and Vice Presidential Election, The Constitution, The Amendment of The 1945 Fundamental Constitution